Behavior and Marketing Mix Influencing Consume Street Food’s Decision in the New Normal Era of Consumers in Nonthaburi Province - Boonyachai, Yootanat (Journal of Humanities and Social Sciences Thonburi University, 2022)
The objectives of this research were: 1) to compare consumers’ street food consumption decision classified by street food consumption behavior. 2) to study the marketing mix (4’Es) and consumers’ street food consumption decision and 3) to study the marketing mix (4’Es) influencing consumers’ street food consumption decision. The sample was 405 street food consumers in Nonthaburi Province. The research instrument was a questionnaire. The statistics used were frequency, percentage, means, standard deviation, t-test, One-Way ANOVA, Least Significant Difference and multiple regression analysis with statically significant level of 0.05. The results showed that 1) there was one aspect of the food consumption behavior was the importance of different food consumption caused different street food consumption decision with statistically significant level at the 0.05. Food consumption behavior in the other 6 aspects, there were no different street food consumption decision. 2) the first priority regarding the marketing mix (4’Es) was exchange, which had a high level on street food consumption decision. 3) Marketing mix (4’Es) on Experience (β=0.172), Everyplace (β=0.158) and Evangelism (β=-0.151) were able to predict 8.2 percent of variation in street food consumption decision in the new normal era of consumers in Nonthaburi Province with statically significant level of 0.05